The Influence of the Quality of Human Resources, Education and Training, and the Village Financial System (Siskeudes) on the Quality of Village Financial Reports - Devi Rukmana Sari; Sarwendah Biduri (Indonesian Journal of Cultural and Community Development, 2021)
The purpose of this study was to determine the effect of the quality of human resources on the quality of village financial reports, the effect of education and training on the quality of village financial reports, and the village financial system (siskeudes) on the quality of village financial reports. This study uses a quantitative approach. The sample used in this study was 100 village officials. The data analysis technique used is multiple linear regression analysis, coefficient of determination (R2). Partial correlation coefficient, t test, F test using SPSS for windows program. The data of this study were obtained from the results of the tabulation of the distribution of the questionnaire using a Likert scale. The results of this study indicate that the quality of human resources has a significant effect on the quality of village financial reports, education and training have a significant effect on the quality of village financial reports, and the village financial system (siskeudes) has a significant effect on the quality of village financial reports.